PENGARUH PELATIHAN TERHADAP SIKAP KERJA, SIKAP TERHADAP PERUBAHAN DAN KINERJA PETERNAK (Studi Pada Peternak Se-Indonesia) - Apriwandi Apriwandi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2021)
This study aims to explore the relationship between work attitudes, including attitudes This study aims to explore the relationship between attitude towards work and attitudes towards change and work achievement and explore how the training pattern and technical guidance stimulate work values and work attitudes of farmers in Indonesia. The samples in this study were those involved in the livestock industry in Indonesia, i.e., breeders, veterinarians, and staff of the Ministry of Agriculture (Head of the Center for Livestock Research and Development) that consisted of 220 respondents. The study results provide evidence of a positive relationship between work attitudes and attitudes towards change as indicated by an increase in work value (work achievement). Thus, cost accounting training for farmers can improve work performance if there is an increase in work attitude and attitudes towards changes by the livestock industry players in Indonesia.